Sequential injection-LOV format for peak height and kinetic measurement modes in the spectrophotometric enzymatic determination of ethanol: Application to different alcoholic beverages - Vidigal, Susana S. M. P. (2010)
The objective of this work was to make a contribution to study the potential of the sequential injectionlab-on-valve (SI-LOV) format for the miniaturization of enzymatic assays, by using different measurement modes (peak height and initialrate-based measurement). A LOV system was developed for the enzymatic assay of ethanol in beverages, based on the conversion of ethanol to acetaldehyde by alcohol dehydrogenase, using spectrophotometric detection. The use of the kinetic-based approach permits the applicability of the enzymatic determination to samples with intrinsic absorption, with a higher determination throughput. A linear dynamic application range up to 0.040% (v/v)was achieved for both initial rate and for the peak height measurement, with good repeatability (R.S.D. < 5.0% and <1.0%, respectively). Enzyme, NAD+, buffer and sample consumption per assay were 0.12U, 0.066 mg, 150 and 15µL, respectively. The determination rate achieved was 37 and 27 determinations h−1 for the initial rate and for the peak height measurement, respectively. The results obtained for several alcoholic beverages, including a certified sample material, were not statistically different from those obtained by the reference procedures.